Designing healthy futures: involving primary school children in the co-design of a health report card. Issue 4 (2nd October 2019) - Scharoun, Lisa; Davey, Rachel; Cochrane, Tom; Mews, Gregor
ABSTRACT: Establishing and maintaining a healthy lifestyle is essential in assuring a child's health and wellbeing over the life-course. Of national concern in Australia is the fact that nearly three in every 10 children and young people are overweight or obese. Childhood overweight/obesity is also a global concern. The energy deficit needed to reverse the trend in childhood obesity may be quite small for most children however that intervention should start early and be sustained. Children can be active participants in creating new social norms for society but this is not often recognized. Society tends to position children as passive spectators and/or gives them superficial roles in creating artifacts for use in schools and other institutions such as health care centers. In order to support healthy lifestyle change in primary school settings, a Physical Activity and Lifestyle Management (PALM) report card system for progression, monitoring and reporting of anthropometric achievement standards for children has been proposed. In order for this system to be an effective communication tool it needed to be designed in a way that would not only be visually appealing and easy to use but would also allow parents and children to take a sense of ownership of the design and enable it to be accepted by the wider community. This paper describes and discusses the co-design approach that enabled children and designers to develop the PALM card and to provide some understanding of children's perceptions of healthy habits and behaviors.